Cardiac Calcified Amorphous Tumor of the Mitral Valve Presenting as Transient Ischemic Attack - Mohammad Abbasi Teshnizi; Atefeh Ghorbanzadeh; Nahid Zirak; Babak Manafi; Aliasghar Moeinipour (Case Reports in Cardiology)
Cardiac calcified amorphous tumors (CATs) are an extremely rare nonneoplastic intracardiac masses. They have been reported in the literature in only a few cases. Thus, the incidence, pathogenesis, and best approach to the treatment are not certain. We report a case of CATs on the atrial surface of the anterior mitral valve leaflet in a 37-year-old female who was diagnosed by histopathological examination after surgical removal.